A mulher trabalhadora em busca de direitos na Justiça do Trabalho do Rio Grande do Sul : desafios da emancipação feminina nos anos 1941-1946 - Schneider, Giselda Siqueira da Silva (2014)
To present research treats of the implementation of the hard-working woman's rights in the Justice of the Work of Rio Grande do Sul, in the temporary cutting from 1941 to 1946. For so much, it uses as theory the field of study of the History of the Women, when rescuing about the path of those studies and the contributions to understand the relationship between the women's movement and the subject of the rights protected by the State. The used primary sources were the processes ended preserved and that they are in the Memorial of the Justice of the Work of Rio Grande do Sul. Therefore, in the analysis they consist petition of the existent Labor Sticks in the period, in the occasion denominated Committees of Conciliation and Judgement, of the cities of Porto Alegre, Rio Grande, São Jerônimo and Pelotas. The Justice of the Work that appears for initiative of President Getúlio Vargas is instituted by the Constitution of 1934, is inaugurated in 1941 and she integrates into the Judiciary Power only in 1946. In the context of a politics of ordination of the job market, where the labor legislation, social and syndical safety has prominence, the Justice of the Work grows inside of the ideology of a corporate State that it tries to outlaw the fight of classes and to offer to the litigants a peaceful form of solution of the labor controversies. When considering the positivization of the protective legislation in relation to the woman's work in Brazil among 1930 to 1945, among other rights, as the right to the vote in 1932, he wants to verify on her the access of the women the that judicial instance. Such a project is justified because although the conquest of rights in the plan of the law, still existed in the social extent a strong resistance to the woman's idea in work out of the domestic atmosphere. The research in such sources also intends, to demonstrate the historical value of the documents, in the present case, of the lawsuits under the guard of the Memorial of the Justice of the Work in Rio Grande do Sul, ally to the research and the bibliographical revision. It is sought to understand a little more, of the workers' from Rio Grande do Sul universe in the period and the possible relationship of the Justice of the Work concerning the promotion and effectiveness of the social rights